Is Preoperative G-Tube Use Safe for Esophageal Cancer Patients?. (18th May 2020) - Saeed, Sabrina M.; Fontaine, Jacques P.; Dam, Aamir N.; Hoffe, Sarah E.; Cameron, Miles; Frakes, Jessica; Mehta, Rutika; Gurd, Erin; Pimiento, Jose M.
Abstract: Objective: Gastrostomy tubes (g-tubes) have been used with caution prior to esophageal resection due to the risks of inoculation metastasis and of injury to the gastric conduit used for reconstruction. In this study, we aim to evaluate the safety of preoperative g-tube placement by comparing outcomes in patients undergoing esophageal resection with and without prior g-tube use. Method: We retrospectively reviewed our institution's database of 1113 esophagectomies performed between 1994 and 2018. We included only patients who received neoadjuvant therapy and identified 65 patients who received preoperative nutritional support through a g-tube (GT+) and 657 who did not (GT–). Demographics, postoperative complications, survival, and cancer recurrence rates were compared between GT + and GT– using Chi-squared and Kaplan–Meier survival analyses. Results: Seven-hundred twenty-two patients (122 female, 600 male) with a median age of 63.2 (28.2–86.3) met our inclusion criteria. Between GT+ (n = 65) and GT– (n = 657), there were no significant differences in anastomotic leak rates (11.5% vs 10.9%; p  = 0.901), postoperative mortality (3.1% vs 3.9%; p  = 0.765), or overall complications (63.1% vs 65.1%; p  = 0.746). GT + was associated with a significantly lower overall survival compared to GT– (32.5 m vs 92.9 m; p  = 0.003), and tumor recurrence rates were similar (30.6% vs 31.8%; p  = 0.851). There were no cases documenting damage to the gastric conduit caused by prior g-tube placement. Conclusions: G-tube usage was not associated with increased tumor recurrence, anastomotic leak rates, or overall complication rates in this study. Our data suggest that g-tube usage is safe for patients with esophageal cancer requiring preoperative nutrition.